Effect of compression modalities for recovery on wrestlers' biomarkers in one day tournament - Mohamed S. Ghoraba; Marwa F. Ghazy (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2019)
The aim of the study was to investigate the effect of different compression modalities as to recovery enhancement on some biomarkers in wrestlers. Serum creatinine, lactic acid and glucose level were tested in elite wrestlers before a match-up, 3 minutes post-match up and 19 minutes after applying recovery compression model. The results showed insignificant differences between pre-post 3-minute tests among research groups due to sample equality, 3-minute and 19-minute post match-up tests showed efficacy of compression technique in enhancing recovery in sake of 160/20 mmHg compression modality with enhancement percentage of 16.614% for serum creatinine, 43.214% for lactic acid and 22.505% for glucose level. The compression band with 160/20 mm Hg exceeds recovery after match-up.